Oleic Acid-Ligated Co0.7 Doped Ca0.3fe2o4 Nanoparticles: A Synergistic Approach for Enhanced Wastewater Purification and Magnetic Hyperthermia Applications - Radhalayam, D (Elsevier B.V., 2025)
Magnetic nanoparticles have garnered considerable interest due to their multifunctional capabilities in various applications. This study focuses on the synthesis of oleic acid-anchored Co0.7Ca0.3Fe2O4 spinel nanoferrites, which were synthesized by the thermal decomposition of metal acetylacetonates in octadecene using oleic acid and oleylamine as surfactants. These nanoparticles exhibit a well-crystallized structures, narrow size distribution, and biocompatibility. The photocatalytic properties of the nanoparticles were evaluated through the degradation of the anionic Orange II and the cationic methylene blue (MB) dyes under UV light. Significant degradation efficiencies were observed; Orange II showed 92.4 % degradation within 60 min, whereas MB achieved 89.8 % over 300 min. Additionally, the specific absorption rate (SAR) of the magnetic fluids was determined via adiabatic calorimetry under varying magnetic fields and concentrations, revealing a maximum SAR of 418 W/g at a concentration of 3 mg/mL and a magnetic field of 475 Oe. © 2025 Elsevier B.V.